UJI KEBENAR AN ENAM KULTIVAR CABAI KERITING (Capsicum annuum L.) - , FAHRUDIN; , Dr. Panjisakti Basunanda, SP., MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Chili pepper is among the most important vegetables in Indonesia, notably for its widespread utilisation and high economic value. The demand to plant this South American-origin vegetable is always high, raising reported fraudulent practices in seeds supply, in the form of intentionally reducing or changing the cultivar purity, which violate good business practices. To combat such foul practice, regular control on seeds that sold in the farmer level needs to be done. Unfortunately, standard procedure for such control has not been provided in Indonesia. This work is conducted with aim to provide procedures that can be considered preliminary and may subject to later development. Six chili pepper cultivars were collected from open market. 'Lado', which is a popular product of East West Seed, was obtained from Medan (A1), Makassar (A2), Tangerang (A3), and Mataram (A4) markets. 'Princess-06', a product of PT Benihinti Suburintani, was obtained from Lembang (B1), Sleman (B2), and Mataram (B3). Four subsequent cultivars were products of PT Oriental Seed Indonesia. 'OR Charming' was obtained from Serang, and 'OR Twist 22' , 'OR Twist 33' , and 'OR Twist 42' were obtained from Magelang. Two locations were chosen for the study: Krukut, Depok, West Java, from May to October in 2012 (+ 90 m above sea level) and Cikole, Lembang, West Java, from May to November 2012 (+ 1.250 m above sea level). Uniformity within and among market sources within single cultivar was tested based on qualitative and quantitative phenotypic characters. Based on the same characters, conformity to the description of the respective cultivar registration was also tested. Uniformity within and among market sources of the same cultivar was shown to be legitimate, based on qualitative as well as quantitative characters. The result was based on analysis of variance for quantitative traits and supported with principle component analysis. Threshold level for quantitative traits, which allow 5% maximum deviation from total samples, provided the decision for qualitative traits. True to description test based on qualitative characters concluded that almost all traits supported conformity to the respective cultivar description. Some discrepancies were assumed as the results of misinterpretation. However, quantitative characters showed invariable lower-than-described performance in both locations, although the decrease was observed for all samples on all quantitative variables observed, with only small amount of (higher) outliers. The result led to suspicion that the performance test for cultivar registration had been conducted under quite different environment than this work and raised the issue of unstability.